Simultaneous detection of multiple DNA damage types by multi-colour fluorescent labelling. Issue 76 (4th September 2019) - Torchinsky, Dmitry; Michaeli, Yael; Gassman, Natalie R.; Ebenstein, Yuval
Abstract : Specific and simultaneous quantitation of DNA adducts is a major obstacle. Using repair enzymes, we present a protocol to quantify two types of DNA lesions simultaneously on the same DNA molecule and examine repair dynamics by single-molecule imaging. Abstract : Herein we present an assay allowing concurrent detection of oxidative DNA damage and photoproducts. We apply DNA repair enzymes specific for each lesion type to incorporate spectrally distinct fluorescent nucleotides, enabling simultaneous quantification of the lesions on individual DNA molecules. We follow the repair of both damage types in skin cells exposed to artificial sunlight.